A growing bacterial colony in two dimensions as an active nematic. Issue 1 (December 2018) - Dell'Arciprete, D.; Blow, M.; Brown, A.; Farrell, F.; Lintuvuori, J.; McVey, A.; Marenduzzo, D.; Poon, W.
Abstract How a single bacterium becomes a colony of many thousand cells is important in biomedicine and food safety. Much is known about the molecular and genetic bases of this process, but less about the underlying physical mechanisms. Here we study the growth of single-layer micro-colonies of rod-shapedEscherichia coli bacteria confined to just under the surface of soft agarose by a glass slide. Analysing this system as a liquid crystal, we find that growth-induced activity fragments the colony into microdomains of well-defined size, whilst the associated flow orients it tangentially at the boundary. Topological defect pairs with charges $$± {\textstyle{1 \over 2}}$$ ± 1 2 are produced at a constant rate, with the $$+ {\textstyle{1 \over 2}}$$ + 1 2 defects being propelled to the periphery. Theoretical modelling suggests that these phenomena have different physical origins from similar observations in other extensile active nematics, and a growing bacterial colony belongs to a new universality class, with features reminiscent of the expanding universe. Rod-shaped bacteria are an example of active matter. Here the authors find that a growing bacterial colony harbours internal cellular flows affecting orientational ordering in its interior and at the boundary. Results suggest this system may belong to a new active matter universality class.